GENEXPERT ® TECHNOLOGY A BREAKTHROUGH FOR DIAGNOSIS OF TUBERCULOUS PERICARDITIS AND PLEURITIS IN LESS THAN TWO HOURS - Hamid Mahmood; Talmeez Zaib; Zafar Hayat Maken (Journal of University Medical & Dental College, 2018)
ABSTRACT:BACKGROUND: Diagnosis of Tubercles Pericarditis and Pleuritis remains the greatest challenge for clinicians. WHO has recommended GeneXpert MTB/RIF assay as a screening test for substitution of conventional methods for the initial diagnosis and prognosis of the extra pulmonary and pulmonary tuberculosis in developing countries. OBJECTIVE: To ﬁnd out the diagnostic validity of GeneXpert assay for detection of Myco-bacterium tuberculosis in the pericardial and pleural eﬀusion samples, keeping MTB culture as “Gold Standard”. MATERIAL AND METHODS: The total number of 286 samples of eﬀusions (pericardial 128, pleural 158) were received, and processed for Zn smear microscopy, LJ culture, GeneXpert MTB/RIF assay according to standard protocols. Eﬃcacy for the detection of MTB was evaluated comparatively. RESULTS: Out of 286 eﬀusions samples AFB was detected by Zn smear in 11 (3.8%) samples while GeneXpert detected MTB in 43 (15.0%) and LJ culture 51 (17.8%). Zn smear showed sensitivity 18.2% , speciﬁcity , 98.1% , Positive predictive value 81.8% , Negative predictive value 85.4 % , in comparison GeneXpert showed high sensitivity 84.3%, speciﬁcity 100%, with Positive predictive value 100% and Negative predictive value 96.7%. CONCLUSION: GeneXpert assay is an innovative tool in resource limited settings for prompt detection of MTB along with drug résistance. It is deﬁnitely an attractive point of care testing, with high sensitivity and speciﬁcity along with turnout time of two hours, which facilitates timely diagnoses and appropriate management of tuberculous Pleuritis and Pericarditis.